Human Nervous System:Depth Classification Version of CC - Seetharama, S. (Journal of Information and Knowledge, 1973)
A Depth Classification Version of Colon Classification (=CC) for Compound Subjects going with the Host Subject "L,7 Nervous System" is given. The methodology for the design of freely-faceted scheme for classification and the current version of the notational system of CC have been used. A schedule of Special Components for forming Compound Isolates is also given. An Alphabetical Index to the schedules, a list of 50 examples classified according to the scheme for classification, and an alphabetical index to the subjects are given.